Sintesis Pigmen Merah Hematit (α-Fe2O3) dari Pasir Besi dengan Metode Kopresipitasi dan Hidrotermal: A Review - Lestari, Destriani Umi (Asian Journal of Science, Technology, Engineering, and Art, 2023)
The purified natural iron sand contains magnetic dioxide particles to produce ferric ions (Fe3+) which can be used as precursors for the synthesis of the red pigment hematite. Hematite red pigment synthesis was carried out by coprecipitation method with NaOH precipitating agent and hydrothermal.The optimum pH of the hematite red pigment synthesis reaction using the coprecipitation method is pH 6. At pH 6 it will produce a hematite red pigment with higher brightness. By the hydrothermal method Fe3O4 added 50 mL HCl (12,063 M) in a beaker. The filtrates are added boric acid with varying concentrations of 0.1 M; 0.3 m; 0.5 M and 1.0 M at a volume ratio of 1:1. Gradually the solution is supplemented with NH4OH 6 M until a solution with a pH of 8 is obtained at a constant temperature of 70oC. The formed precipitate is put in the microwave for 10 minutes with a pressure of 90P. The characterization was carried out using XRD to see the crystal structure of the product and UV-Vis to see the absorption wavelength.und is the anatase phase.